Relationship Between Family Support and Compliance in Taking Hypertension Medication - Siallagan, Erpina; Tampubolon, Lindawati F.; Ginting, Agustaria (LLDIKTI Wilayah 1, 2024)
Hypertension is a degenerative disease that cannot be cured but can be prevented from recurring by taking hypertension medication and implementing a healthy lifestyle. This lifelong care process requires family support, especially in improving blood pressure. This study aims to identify the relationship between family support and medication adherence in hypertension patients at the Harapan Hospital Polyclinic, Pematang Siantar. This correlation study uses a cross-sectional approach. The study population was hypertension patients who were treated at the Harapan Hospital Internal Medicine Polyclinic with a purposive sampling technique of 51 respondents. Family support was found with an average score of 32.61, with a standard deviation of 6.226. Meanwhile, medication adherence obtained an average score of 4.53 with a standard deviation of 2.572. Based on the Pearson Product Moment test, a p-value of 0.001 (<? = 0.05) was found with an r value of 0.715, indicating that there is a relationship between family support and medication adherence in hypertension patients with a strong positive relationship. It is expected that hypertension sufferers will diligently control their blood pressure and remain compliant in taking hypertension medication to maintain blood pressure stability so that unwanted things such as complications do not occur.